FINANCIAL FRAUD AT ENTERPRISES AND METHODS OF ITS PREVENTION (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Regardless of the form of ownership, fraud at enterprises is a typical phenomenon not only for Ukraine, but also for the whole world. The unstable economic situation of Ukraine gives rise to the subjective factor of fraud - the desire of employees and contractors to preserve the quality of life and the level of income. Thus, the objective factor in the occurrence of fraud is significant changes in the system of distribution and pricing of goods, which give a powerful impetus to the spread of corporate fraud.Corporate fraud is a type of economic crime that covers all the various means created by human ingenuity to obtain an unfair advantage of one person over another through deception, trickery, breach of trust, concealment of the truth. In the work, the authors considered approaches to the interpretation of the essence of fraud and the main characteristics of this phenomenon, identified the most common types of financial crimes at enterprises. The main trends in the number of financial frauds in the world and in Ukraine in the context of economic downturns are analyzed. Schemes of professional fraud in companies were systematized, methods of building a reliable system of control and risk management at domestic enterprises were studied. The role of internal audit in preventing fraud with the financial resources of the business entity is revealed and it is proposed as an alternative to forensic audit. It is argued that the forensic audit will allow timely determination of the cause-and-effect relationship between cases of fraud and the reasons that caused them; identify and reduce the risks of fraud, illegal actions and unethical behavior of personnel and contractors; assess financial losses resulting from misappropriation and waste of assets, as well as purchases and sales that are unprofitable for a commercial enterprise.
Keywords: financial fraud; enterprises; corruption; financial and reputational losses, forensics.